2019
DOI: 10.1055/s-0038-1675392
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic Voice Modifications in Individuals with Parkinson Disease Submitted to Deep Brain Stimulation

Abstract: Introduction Subthalamic nucleus deep brain stimulation (STN-DBS) improves motor function in individuals with Parkinson disease (PD). The evidence about the effects of STN-DBS on the voice is still inconclusive. Objective To verify the effect of STN-DBS on the voice of Brazilian individuals with PD. Methods Sixteen participants were evaluated on the Unified Parkinson Disease Rating Scale—Part III, and by the measurement of the acoustic modifications in on and off conditions of stimulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Before applying feature extraction, all the recordings from both databases were trimmed down to one second discarding any leading or trailing silence. This length has been considered sufficient to extract speech features from sustained vowel phonations by other authors [ 40 ]. Voice recordings were edited using Audacity software (release 2.0.5).…”
Section: Methodsmentioning
confidence: 99%
“…Before applying feature extraction, all the recordings from both databases were trimmed down to one second discarding any leading or trailing silence. This length has been considered sufficient to extract speech features from sustained vowel phonations by other authors [ 40 ]. Voice recordings were edited using Audacity software (release 2.0.5).…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have explored the impact of ON/OFF stimulation on phonation and articulation in PD patients undergoing DBS [97, 169,170,[183][184][185][186][187][188][189][190][191][192][193]. Some studies yielded positive effects of DBS on speech parameters, such as a reduced jitter and noise-to-harmonics ratio, improved fundamental frequency (F0), and vocal response to pitch shift, as well as increased phonation time and syllable length [184,185,189,193].…”
Section: Phonation and Articulationmentioning
confidence: 99%
“…Some studies yielded positive effects of DBS on speech parameters, such as a reduced jitter and noise-to-harmonics ratio, improved fundamental frequency (F0), and vocal response to pitch shift, as well as increased phonation time and syllable length [184,185,189,193]. Conversely, other studies found negative effects of DBS, such as diminished speech intelligibility, deteriorated articulation, and reduced vocal response magnitudes [97, 106,169,170,188,[190][191][192]. Additionally, some others have showed conflicting results for various speech measures [170,183].…”
Section: Phonation and Articulationmentioning
confidence: 99%
“…These side-effects include muscle contractions, voice changes, deleterious mood and cognitive changes, memory impairments, seizures, and more. [18][19][20][21][22][23] While side effects or returning symptoms caused by a change to the stimulation setting may be briefly tolerable under the supervision of a clinician, they could be unsafe or detrimental during daily living activities. As a consequence, data-driven methods must be designed to actively learn and avoid unsafe parameter space regions for any automated or unsupervised optimization approaches.…”
Section: Introductionmentioning
confidence: 99%